Didactic Engineering as a research method in physics teaching (2021)
Several mathematical concepts have application in physics; this paper reports the results of a pedagogical investigation based on the methodology known as didactic engineering, which has been proposed with the aim of improving the skills exhibited by a group of eleventh grade students from a private institution in the interpretation of kinematic graphs. The concept of the slope of the straight line and how this mathematical concept can represent velocity or acceleration according to the variables considered in the kinematics graph provided was enhanced in the pedagogical intervention. This methodology offers a process of internal validation, after comparing the results obtained in a knowledge test at two different points in time (pre-test and post-test). The results allowed us to identify improvements in all students in terms of basic kinematics graph interpretation skills, and a group of students stood out by advancing in more complex reasoning and interpretation processes. These results contribute to the improvement of the pedagogical practices of Physics teachers at secondary and middle school levels, making them more competent when they enter higher education.